Low-cost spray-processed Ag1-xCuxInS2 nano-films: Structural and functional investigation within the Lattice Compatibility Theory framework - YUMAK YAHŞİ, AYŞE (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
This work deals with some structural and optical investigations about CuxAg1-xInS2 alloys sprayed films and the beneficial effect of copper incorporation in AgInS2 ternary matrices. The main purpose of this work is to obtain the band gap energy E-g as well as different lattice parameters. The studied properties led to reaching minimum of lattice mismatch between absorber and buffer layers within solar cell devices. As a principal and original finding, the lattice compatibility between both silver and copper indium disulfide structures has been proposed as a guide for understanding kinetics of these materials crystallization. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Alloys; Vapor deposition; X-ray diffraction; Lattice dynamics; PHYSICAL-PROPERTIES; OPTICAL-PROPERTIES; THIN-FILMS; AGINS2; CONSTANTS